Variations of graphene nanotube membrane support layer in outlet flux of PAFO system - Javarani, Leila; Malakootian, Mohammad; Hassani, Amir Hessam; Javid, Amir Hossein (Journal of the University of Zulia, 2020)
The PAFO system is a solution in the desalination of seawater using a hydraulic pressure of 5 bar, which competes with the FO system (direct osmosis). The project includes four stages of pilot construction, entrainment detection, graphene nanotube membrane synthesis and, finally, efficiency determination and outflow modeling of the PAFO system. High Flux is the most important parameter of the system test for practical application. According to the results, the highest flow of current (120 l / m2.hr) was calculated at the osmotic pressure of 55, indicating a 50% increase in the flow of water with KOH fertilizer as entrainment solution and membrane of low thickness backing layer. Outflow values were calculated using theoretical modeling (MATLAB software). The results show the consistency of the outflow with the flow of the proposed chi model.